Conservation Science and Practice Must Engage With the Realities of Complex Tropical Landscapes - Boedhihartono, Agni K.; Bongers, F.; Boot, R.G.A.; Dijk, J. van; Jeans, H.; Kuijk, M. van; Koster, H.; Reed, J.; Sayer, J.; Sunderland, T.C.H.; Turnhout, Esther; Vianen, J. van; et al. (SAGE Publications, 2018)
There is a growing disconnect between the international conferences where grand solutions for tropical conservation are designed and the complex local realities in tropical landscapes where plans need to be implemented. Every tropical landscape is different and no “one size will fit all.” There is a tendency for global processes to prescribe simple generalized solutions that provide good sound bites that can be communicated with political actors and the media. Sustainable outcomes in tropical landscapes require locally adapted, unique approaches supported by long-term processes of learning and adaptation. Tropical biologists and conservationists can play a key role by establishing effective local–global links and by directly engaging in local policy discourses while remaining connected to evolving political imperatives.